Analyze Rainfall Distribution During Tropical Cyclones in Vietnam Using TRMM 3B42 Satellite Data - Thanh Hang, Vu; Ngoc Nghia, Nguyen; Thanh Ha, Pham; Thi Thanh Nga, Pham (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1SDO - 10.25073/2588-1094/vnuees.5395, 2025)
In this study, the information of 63 tropical cyclones (TCs) landfalling in Vietnam during 2000 and 2019 is collected to investigate the spatial and temporal distribution of TC-induced rainfall in relation to ENSO phases and landfall directions. The results indicate that ENSO exhibits distinct influences at different stages of the TC lifecycle: the La Niña phase is associated with increased rainfall over a broad area before landfall, whereas the El Niño phase is linked to the peak rainfall intensity occurring at the time of landfall, followed by a rapid decline. Asymmetric TC-induced rainfall structures are more evident during El Niño phase, while in La Niña phase, they typically exhibit more spatially uniform and widespread rainfall distribution. Landfall direction also indicates significant differences in TC-induced rainfall characteristics. TCs landfalling from the southwest tends to produce more intense and localizes peak rainfall near the TC center, which rapidly weakens after landfall. In contrast, TCs landfalling from the west and northwest generate broader rainfall areas with longer post-landfall persistence. Overall, landfall direction makes a greater influence on the structural variation of TC-induced rainfall than the ENSO phases.